Extraosseus Ewing's Sarcoma of the Forearm - Bansal, Kuldeep (Cureus, 2020)
A 22-year-old female presented with painful, progressive swelling of the right forearm for six months. Physical examination revealed a 7 cm x 5 cm firm, tender soft-tissue swelling over the anterior aspect of the right proximal forearm with normal overlying temperature. X-rays showed increased soft tissue shadow but without any bony involvement. Serum alkaline phosphatase, serum lactate dehydrogenase, and leukocyte count were raised. MRI of the right forearm revealed enhancing soft tissue lesion with internal hemorrhagic and necrotic components involving the flexor carpi radialis muscle. Core biopsy confirmed the diagnosis of extraosseus Ewing’s sarcoma. Neoadjuvant chemotherapy, wide local tumor excision, and adjuvant chemotherapy and radiotherapy were done. The patient then lost to follow-up and presented again after six months with a fungating mass and neurovascular involvement for which an above-elbow amputation was done. We, through this case report, aim to discuss the clinical and radiological findings, line of management, and the importance of early detection and treatment and a regular follow-up for extraosseus Ewing's sarcoma of the extremity.